BALANCE HÍDRICO EN LA CUENCA ALTA DEL RíO REVENTAZÓN, COSTA RICA - Vargas Sanabria, Asdrúbal (2011)
A water balance was established for the upper part of the Reventazón river basin. The basin is controlled by 13 rain gauge stations. The rainy season ranges from May till November with an average precipitation of 3412mm/y. The area of highest rain-fall is controlled by the station T-Seis.The surface run-off is registered by the following stations: La Troya, Palomo, La Suiza and Angostura. The maximumsurface run-off of about 300 m3/s was measured at the Angostura.station The minimum dry season surface run-off va-lues are only 10% of this amount. The observation period ranges from 1977 to 1993 showing an annual average of 77to 110 m3/s. The average of the total period is 90 m3/s.Depending of the subcatchment area the rate of surface run-off to precipitation differs from 48% to 82% and concerning to this values the evapotranspiration varies from 18% to 52%.The groundwater discharge was determined by the method of Kille (1970) and Wundt (1953). The calculated valuesvary in the range of 15 l/s/km2 at La Troya and 50 l/s/km2 at Palomo.